Perception of distance learning in Bangladeshi tertiary education: prospects and obstacles in the Covid-19 era - Md. Rahat Khan; S. M. Sabbih Hossain (Journal of Social, Humanity, and Education, 2021)
Purpose: The key purpose of the study is to understand the university students' perception of a sudden distance learning platform from Bangladesh (a least developed countries' perspective). Research methodology: This particular study has employed a qualitative research method with the support of interview and observation methods. The study has selected 20 University students as a sample size based on purposive sampling. Results: The findings provide a vivid outline of the current situation of the universities- that the students have- over the influence of distance learning on education, technology, their university, course instructors, and themselves. Limitations: The data was qualitative in nature and the study only interviewed the university students but not the other stakeholders of that system; in addition, the study did not triangulate the data with more quantitative data. Contribution: The study makes an important contribution to the literature on the least developed countries' university education, which will benefit Higher Education institutions that are also struggling with the prospects and obstacles of distance learning during and in the post-Covid-19 crisis.